2006
DOI: 10.1088/0268-1242/22/1/s48
|View full text |Cite
|
Sign up to set email alerts
|

Thin germanium–carbon layers deposited directly on silicon for metal–oxide–semiconductor devices

Abstract: We report the growth process and materials characterization of germanium-carbon alloys (Ge 1−x C x ) deposited directly on Si (1 0 0) substrates by ultra-high-vacuum chemical vapour deposition. The Ge 1−x C x films are characterized by transmission electron microscopy, etch-pit density, x-ray diffraction, secondary ion mass spectrometry and electron energy loss spectroscopy. The results show that the films exhibit low threading dislocation densities despite significant strain relaxation. We also present eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…SIMS profiles showed that the carbon segregates toward upper/lower portion of the films near the surface/interface regions. The layers are slightly compressed with a net relaxation of ∼78% and are typically too thin for optical applications but could prove useful for Ge channel MOSFETs . Our deposition experiments using GeH 3 CH 3 were conducted on a single-stage wafer configuration at significantly lower temperatures (360 °C), which precluded any of the side reactions that might lead to carbon contamination.…”
Section: Resultsmentioning
confidence: 99%
“…SIMS profiles showed that the carbon segregates toward upper/lower portion of the films near the surface/interface regions. The layers are slightly compressed with a net relaxation of ∼78% and are typically too thin for optical applications but could prove useful for Ge channel MOSFETs . Our deposition experiments using GeH 3 CH 3 were conducted on a single-stage wafer configuration at significantly lower temperatures (360 °C), which precluded any of the side reactions that might lead to carbon contamination.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the low solid solubility of C in Ge, C tends to segregate toward the interface of Ge 1−x C x /Si substrate and thus limits the defects near the bottom interface. As a result, the upper portion of the Ge 1−x C x layer has a much lower defect density than that of pure Ge grown directly on Si (1 0 0) [7,8]. On the other hand, the in situ Si capping of the Ge 1−x C x layer prevents GeO x formation and passivates the Ge 1−x C x surface.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4b shows a high magnification XTEM of the Ge 1-x C x layer with a Si cap. A etch pit density (EPD) formula modified to work with thin films determine a defect density of 3.0 ×10 5 cm -2 , while the a Ge layer of similar thickness grown over an entire 4" wafer had a defect density of 2.8 ×10 8 cm -2 , and no defects were found on the bulk Ge wafer (23). AFM analysis of the surface shows very low RMS roughness of 3Å, which is among the lowest ever reported for Ge films on Si.…”
Section: Germanium-carbon Directly On Silicon Pmosfetsmentioning
confidence: 99%